INDONESIAN EFL STUDENTS’ PERCEPTIONS ON SYNCRHONOUS AND ASYNCHRONOUS E-LEARNING - Yuliana Friska (Universitas Pahlawan Tuanku Tambusai, 2021)
The use of technology in language learning has been extensively expanded. However, the investigation into the implementation of e-learning through video conferences (synchronous) and learning management systems (asynchronous) particularly in English Language Teaching is still lacking. This study was aimed to investigate the students' perceptions on synchronous and asynchronous e-learning in ELT. Furthermore, the study focused on exploring students’ preferences in using asynchronous and synchronous e-learning resources, and found out students’ view of the need of teachers' presence in the use of e-learning. The method used in this study is an online survey through google form. There were 167 EFL students from accounting department of Universitas Pamulang taking part as the participants. The findings show that students’ perceptions on synchronous and asynchronous e-learning in ELT are positive. This indicates that students are familiar with the use of e-learning as a medium of teaching and learning. Meanwhile, using synchronous e-learning is preferred as it facilitates students have two-way communication with the lecturer. Moreover, the presence of lecturer in e-learning are quite crucial. It shows that no matter how sophisticated the technology is, the presence of teachers is still expected by students.